The Study of Effect Meta Theoretical Curricula's Implementation in Educational Performances of Tehran Universities in Educational Science - Mohammad Reza Sarmadi; Hassan Shahraki Pour; Negar Elhamian (Philippine Association of Institutions for Research, Inc., 2012)
This research program to study the application performance Meta theory Education Faculty of Educational Sciences at the University of Tehran in the year 89-88 has been done. The aim of this study is to examine that faculty of Educational Science, the curriculum specialists and executives, to what extent the common teaching of basic and fundamental vision benefit and which has higher priority. The research in this study is a descriptive survey approach. Measuring the validity and reliability of the questionnaire with 30 questions in 4 Meta theories Miller, Eisner, Hunecke, Walker and Questionnaire in the five-choice Likert scale was determined. Was appointed and Based on simple random sampling method and survey a sample of 87 people and then run the data analysis software SPSS 17. Descriptive statistics were used in the indicator of central tendency. In order to determine the relationship between variables in inferential statistics, k- square method was used. Also the Friedman test analysis was used to determine priorities. The results of the survey questions suggest that Merit-oriented elements in the Miller Performance Training Meta theory Faculty of Educational Sciences at the University of Tehran to other applications. This means that goals in education are used more tangible, more visible and more specific cognitive characteristics.